Neuroscience of human social interactions and adult attachment style - Vrticka, Pascal; Vuilleumier, Patrik (Frontiers in Human Neuroscience, 2012)
Since its first description four decades ago, attachment theory has become one of the principal developmental psychological frameworks for describing the role of individual differences in the establishment and maintenance of social bonds between people. Yet, still little is known about the neurobiological underpinnings of attachment orientations and their well-established impact on a range of social and affective behaviors. In the present review, we summarize data from recent studies using cognitive and imaging approaches to characterize attachment styles and their effect on emotion and social cognition. We propose a functional neuroanatomical framework to integrate the key brain mechanisms involved in the perception and regulation of social emotional information, and their modulation by individual differences in terms of secure versus insecure (more specifically avoidant, anxious, or resolved vs. unresolved) attachment traits. This framework describes how each individual’s attachment style (built through interactions between personal relationship history and predispositions) may influence the encoding of approach versus aversion tendencies (safety versus threat) in social encounters, implicating the activation of a network of subcortical (amygdala, hippocampus, striatum) and cortical (insula, cingulate) limbic areas. These basic and automatic affective mentalization mechanisms are in turn modulated by more elaborate and voluntary cognitive mentalization processes, subserving theory of mind, cognitive control, and emotion regulation capacities, implicating a distinct network (in medial prefrontal cortex, superior temporal sulcus, and temporo-parietal junction, among others). Such research does not only help better understand the neural underpinnings of human social behavior, but also provides important insights on psychopathological conditions where attachment dysregulations is likely to play an important (causal) role.